Analysis of Suboptimal Household Waste Management in Coastal Villages of Sungai Kampar, Bangkinang - Nabila; Herniwanti; Roby Yandri (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Household waste management is a crucial component of environmental health, particulary in rural riverside areas where limited facilities and poor community practices contribute to environmental degraduation. This study aims to identify the conditions and factors contributing to suboptimal household waste management in Sungai Tonang Village. A qualitative descriptive method was uses, involving field observations and semi- structured interviews with village officials, health workers, and residents. Data were analyzed thematically and verified through triangulation of interviews, observations, and supporting documents. The findings indicate that household waste management in the village remains inadequate, as residents commonly dispose of waste into the river, burn it, or bury it due to the lack of waste sorting facilities, temporary storage, and transportation systems. Community knowledge of proper waste management and the 3R concept is low, and the village lacks regulations or institutional structures to support waste management. This situation creaters environmental pollution and increases the potential for vector-borne diseases. The study concludes that ineffective waste management practices in Sungai Tonang Village pose a significant environmental health risk, highlighting the need for regulatory development, facility provision, and ongoing community education to support sustainable waste management practices.